Analysis of the Effect of Human Development Indeks (HDI) and Unemployment Proverty in South Kalimantan Province - Zendato, Novita Ria; Sihaloho, Laura Adelia Mutiara; Nasution, Tuahna Sari; Dongoran, Faisal Rahman (Journal of Business Management and Economic Development, 2023)
Poverty has become a necessary problem that needs to be solved every year because it issuch a complex and multifaceted problem. Poverty is not only related to the response and limitation of employment, but is also influenced by a number of other factors, both of a social and economic nature. This research is a quantitative research conducted in South Kalimantan. With secondary data from the South Kalimantan Central Statistics Agency website in 2022 and analyzed by multiple regression with the Human Development Index (HDI) and the number of unemployed as independent variables and the number of poor as dependent variables. The results showed that higher HDI will reduce poverty.. On the other hand, high unemployment indicates high poverty, which is why it is necessary to help reduce the number of people living below the poverty line.